Electrochemical investigation of mineral electrodes in phosphate-buffered alkaline solution - Erdenechimeg, D; Maralmaa, B; Kashevskii, AV (Mongolian Journal of Chemistry, 2014)
Cyclic voltammetric methods have been applied to study the electrochemical behavior of the sulfide minerals in phosphate-buffered alkaline solution. The redox process of electrodes of sulfide ores was investigated using silicone-impregnated graphite electrode. The cathodic and anodic reaction products in alkaline solution were determined within the potential range of -2V to +2V (vs. Ag/AgCl). The several successive measurement cycles’ voltammograms leads to the appearance of a new anodic peak at E = 450mV, which is absent in the first cycle and curves, as well as other features that appear in cycling, can probably be explained by secondary electrochemical transformations of the products formed by the oxidation of the original pyrite at the interface between the electrode material. DOI: http://doi.dx.org/10.5564/mjc.v15i0.318 Mongolian Journal of Chemistry 15 (41), 2014, p33-35